2010
DOI: 10.1098/rspb.2010.1774
|View full text |Cite
|
Sign up to set email alerts
|

Workers influence royal reproduction

Abstract: Understanding which parties regulate reproduction is fundamental to understanding conflict resolution in animal societies. In social insects, workers can influence male production and sex ratio. Surprisingly, few studies have investigated worker influence over which queen(s) reproduce(s) in multiple queen (MQ) colonies (skew), despite skew determining worker-brood relatedness and so worker fitness. We provide evidence for worker influence over skew in a functionally monogynous population of the ant Leptothorax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 70 publications
1
14
2
Order By: Relevance
“…Our finding also contrasts with previous studies in L. acervorum : dissections and population genetic analyses suggest that the level of skew is more or less fixed within populations, and that colonies maintain their social phenotype when kept under standardized laboratory conditions [18], [19], [25], [26]. Therefore, different levels of reproductive skew have been suggested to be an evolved rather than a behavioral response [19], [49]. This discrepancy might mean that ants from different populations have evolved different thresholds for fighting and dominance behavior, leading to more or less fixed local social organization.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding also contrasts with previous studies in L. acervorum : dissections and population genetic analyses suggest that the level of skew is more or less fixed within populations, and that colonies maintain their social phenotype when kept under standardized laboratory conditions [18], [19], [25], [26]. Therefore, different levels of reproductive skew have been suggested to be an evolved rather than a behavioral response [19], [49]. This discrepancy might mean that ants from different populations have evolved different thresholds for fighting and dominance behavior, leading to more or less fixed local social organization.…”
Section: Discussioncontrasting
confidence: 99%
“…Queen number has also been shown to negatively affect aggression levels toward non-nestmates (Starks, Watson, Dipaola, & Dipaola, 2010), which perhaps suggests a lower threshold of recognition cues in such high-polygynous nests. Indeed, to date the hypothesis of positive nepotism in eusocial insects, specifically in ants, has mostly been refuted (DeHeer & Ross, 1997;Friend & Bourke, 2012;Holzer, Kummerli, Keller, & Chapuisat, 2006;Zinck, Châline, & Jaisson, 2009), except for Formica fusca (Hannonen & Sundström, 2003), but see the criticism by Holzer, Kummerli, et al (2006); e.g., selective brood mortality rather than preferential brood rearing), and Leptothorax acervorum ants (Gill & Hammond, 2011). Boomsma and d'Ettorre (2013) suggested that within-colony kin discrimination might be maintained in a secondary polygyny where there are a high queen turnover and fluctuating relatedness in the colony.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of facultatively polygynous L. acervorum failed to find within-colony kin discrimination during either egg cannibalism by queens (Bourke 1994) or colony fission . In their functionally monogynous study population, Gill & Hammond (2011) found that workers favoured their mother queen as the colony reproductive, although workers may not have used relatedness-based cues to do so. However, potentially nepotistic interactions of workers with queens within facultatively polygynous colonies have not previously been investigated in L. acervorum.…”
mentioning
confidence: 95%
“…If they are nepotistic, workers in the study population are especially likely to use care (as opposed to aggression) to favour a particular queen, because they rarely exhibit aggression towards nestmate queens or interfere with queens' egg‐laying (Bourke ). By contrast, in a population of L. acervorum with functionally monogynous colonies, that is, ones in which there are several mated queens but only one lays eggs at any one time, workers frequently exhibit aggression towards queens (Gill & Hammond ). Previous studies of facultatively polygynous L. acervorum failed to find within‐colony kin discrimination during either egg cannibalism by queens (Bourke ) or colony fission (Heinze et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation